Influence of E-Wom, Price Perception, and Product Quality on VIVO Smartphone Purchasing Decision - Larasaty, Adesgy Tiara; Winarto, Winarto -; Rini, Nur - (Politeknik Negeri Semarang, 2025)
The market share of PT Vivo Mobile Indonesia has experienced fluctuating developments. The main objective of this study is to examine the influence of E-wom, price perception, and product quality, on Vivo smartphone purchasing decisions both simultaneously and partially. Data were collected using a survey method. The questionnaires were distributed to Vivo smartphone buyers and users in the city of Semarang. Multiple linear regression techniques were administered. The results of this study indicated that both simultaneously and partially E-wom, Price Perception, and Product Quality have a positive impacts on Purchasing Decisions. The combined contribution of the three variables to Purchasing Decisions is 73.9% and the remaining 26.1% is likely influenced by other variables